Penggunaan Bahasa Pemrograman Python dalam Analisis Hubungan Peminat dan Daya Tampung Seluruh Prodi di Indonesia Pada PTN Akademik, Vokasi dan PTKIN Tahun 2023 - Erfan, Muhammad; Handika, Ilham; Afriyanti; Mukti, Wiji Aziiz Hari; Ratu, Tursina (Journal of Classroom Action Research, 2024)
This research aims to analyze the opportunities for prospective new students who will enroll in state higher education study programs, both PTN Academic, PTN Vocational, and PT Keagamaan Islam Negeri through ratios or comparisons of capacity and number of applicants for a study program based on region and type of tertiary institution. all study programs in Indonesia. The analysis was carried out using the Python programming language with the involvement of the Numpy, Pandas and MatPlotLib libraries. The analysis process carried out starts from data scrapping, data cleaning, data transformation, and data sorting. The results of the research show that there are 10 study programs with the most interest, namely the Criminology Study Program (University of Indonesia), Communication Sciences (UNJ), Informatics Engineering (Unpad), Informatics Engineering Education (UNY), Digital Business (UNS), Information Systems and Technology ( UNJ), Communication Science (Unpad), Medicine (UGM), Communication Science (UGM), and Communication Science (UPI). Based on region, the lowest ratio is on the island of Java, which means that there is a very large difference between the capacity and those interested in study programs with the capacity being much smaller compared to the number of people interested in study programs on the island of Java. Based on the type of PTN, study programs under vocational state universities are less popular when compared to Academic State Universities.